Magnetic field effects on the forced convection of CuO-water nanofluid flow in a channel with circular cylinders and thermal predictions using ANFIS - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2018)
Numerical simulation of forced convection of CuO-water nanofluid over circular cylinders within a channel was conducted under the influence of a uniform magnetic field by using the finite element method. In the channel, four circular cylinders which are arranged in a two by two matrix configuration are used and they are kept at constant temperature. Effects of various pertinent parameters of the configuration such as the Reynolds number (between 100 and 1000), Hartmann number (between 0 and 10), solid particle volume fraction (between 0 and 0.04) and horizontal distance between the circular cylinder centers (between 0.5 and 8 times of the channel height) on the fluid flow and convective heat transfer were analyzed. The potential use of magnetic field in the reduction of the wake region behind the circular cylinder and augmentation of the heat transfer in the presence of nanoparticle inclusion to the base fluid was examined. It was observed that the established secondary peaks of local Nusselt number along the hot surface for moderate and higher values of Reynolds number reduces with Hartmann number and disappears at the highest value of Hartmann number. When the Hartmann number is increased from Ha = 0 to Ha = 10, 23% of the average heat transfer enhancement is achieved for cylinder which is located in the first row and second column (some distance far away from the wake of the first column cylinder). The average Nusselt number was found to augment by about 17-20 % at the highest and lowest values of Reynolds number and Hartmann numbers for circular cylinders which are placed at (first row first column) and (first row second column). Highly accurate and fast predictions of the average Nusselt number for the circular cylinders are obtained with Adaptive-Network-Based Fuzzy Inference System (ANFIS) modeling.
Keywords: Nanofluid; MHD flow; Finite element method; ANFIS; Convection